Plate Compression Analysis of Woven Spacer Fabrics (Journal of Fiber Bioengineering and Informatics, 2015)
Diameter of spacer filament, thickness of spacer fabric, and warp threads per centimeter and weftthreads per centimeter on plate compression of woven spacer fabric was studied by finite elementmethod. Compression force and strain curves were acquired by ABAQUS software and compressionindices were featured, including compression work, maximum compression force and compression index.Small relative errors of compression indices between experimental and theoretical results demonstratedthat it was feasible to use finite element method to predict plate compression performance of spacerfabric. Woven spacer fabrics with different structure were designed and theoretical results showed thatthe thicker the spacer filament, the greater the three compression indices. Moreover, compression stressdistribution of spacer fabrics indicated that stress of spacer filament was much larger than that of warpthreads and weft threads of surface fabrics.